2019
DOI: 10.4236/wjv.2019.93005
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus and Rotavirus Associated Diarrhoea in under 5 Children from Enugu Rural Communities, South East Nigeria

Abstract: Globally, diarrhoea is the second commonest infectious cause of death in children less than 5 years old. It is estimated that more than one billion diarrhoea episodes occur every year causing up to 700,000 deaths among children younger than 5 years of age. Seventy-two percent of these deaths occur in children below two years and enteric viruses have been recognized as a major cause of childhood diarrhoea. This study was undertaken to determine the prevalence of enteric Adenoviruses and Rotaviruses in children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 34 publications
6
15
0
1
Order By: Relevance
“…Viruses such as rotaviruses and calciviruses that damage the intestinal epithelium also cause fluid loss. Besides, they have more tendency to cause fever, vomiting and watery stools without blood and mucus (Tagbo et al, 2019). Usually, cases of watery diarrhoea run an acute but brief (1-3 days) self-limiting duration.…”
Section: Types Of Diarrhoea I Acute Watery Diarrhoeamentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses such as rotaviruses and calciviruses that damage the intestinal epithelium also cause fluid loss. Besides, they have more tendency to cause fever, vomiting and watery stools without blood and mucus (Tagbo et al, 2019). Usually, cases of watery diarrhoea run an acute but brief (1-3 days) self-limiting duration.…”
Section: Types Of Diarrhoea I Acute Watery Diarrhoeamentioning
confidence: 99%
“…Children below five years of age have the most at risk from foodborne pathogens, including Shiga toxin-producing Escherichia coli O157, Campylobacter, Shigella, Yersinia, Salmonella, and Cryptosporidium (Liu et al, 2014a, b;Kotloff, 2017). In the past few decades, the awareness in handwashing has tremendously reduced the burden of diarrhoea caused by enteric bacteria and protozoans, yet, it has less impact on diarrhoea caused by viruses (Tagbo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 1251 results pooled from unique searches, 23 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] of them met the criteria for the selection of studies. Of the 23 studies that were included, ∼69.6% (16/23) were cross-sectional studies while 30.4% (7/17) [12, 19-22, 24, 27] were case control studies but only five [12,19,20,22,24] reported the necessary data to be added to the case-control analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nuestros resultados concuerdan con los datos de Farfán et al, (2020) quienes detectaron patógenos entéricos en niños menores de 5 años, encontrando que los principales microorganismos causantes de enfermedades gastrointestinales son virus, especialmente norovirus y rotavirus; bacterias como Escherichia coli enterotoxigénica y parásitos como Cryptosporidium. En ese contexto, estudios afirman que la mayoría de las diarreas bacterianas entéricas son originadas por cepas de Escherichia coli, Salmonella y Shigella, entre otras; y sugieren que el incremento de hábitos higiénicos respecto al lavado de manos ha disminuido los episodios diarréicos causados por bacterias entéricas y protozoos, pero han tenido menos impacto sobre las infecciones causadas por virus (Tagbo et al, 2019;Ugboko et al, 2020).…”
Section: Discussionunclassified